Social-Emotional Skills of Elementary School Students: A Comparative Analysis Based on Ability Levels (HAS vs STD) in Rural and Urban Areas - Wulan Nurhidayah; Anggi Aulia; Khaylila Najwa Afifah; Shofiyatun Hasanah; Feyza Acar (CV. Akademi Merdeka, 2026)
Student development in elementary school is not based solely on academic ability but also on social-emotional skills (SES), which support self-regulation, peer relationships, and adaptation to school demands. Comparative evidence on how SES varies according to cognitive ability level and place of residence remains limited. This study analyzes differences in SES among elementary school students based on ability level (High-Ability Students/HAS vs. Standard Students/STD) and residential context (rural vs. urban), including the interaction between the two. A comparative quantitative approach with a 2x2 factorial design was used. Data were collected from 240 fourth- and fifth-grade students (103 HAS, 137 STD) using the Fair Cultural Intelligence Test (CFIT), a sociodemographic questionnaire, and the EACSE-CA scale, which consists of five dimensions of SES. The data were analyzed using descriptive statistics, Cramer’s V, Levene’s test, MANOVA with Pillai’s Trace, and univariate F-tests. Ability level significantly affected all five SES dimensions (F = 4.255, p = 0.001, partial eta squared = 0.084), while residence and the ability-residence interaction were not significant. HAS students scored higher than STD students in basic skills, interpersonal relationships, problem-solving, and emotional regulation, with no difference in goal-setting. SES differences are driven more by cognitive ability level than by residential area. The study enriches the empirical literature on elementary students’ SES through a novel comparative design integrating CFIT and sociodemographic data, offering a foundation for adaptive, ability-sensitive social-emotional learning strategies applicable across both rural and urban schools.